Significados acerca de la atención educativa en el aula regular a niñas y niños en situación de discapacidad en tres instituciones educativas (2011)
This research aimed at understanding the meanings about the educational services in the regular classroom for children with disabilities in three educational institutions. To achieve this, a qualitative research developed from some guidelines of the ethomethodology was proposed. The information was obtained through research strategies such as participant observation, depth interviews, the story and understanding of documents involving those who are considered key players in providing education in the regular classroom for children with disabilities: children, parents or guardians, teachers and directors of institutions. This information was systematized through content analysis of categorical type, encoding and cast in matrixes. As results of the development of this research, the meanings were identified from three subcategories: canonical, exceptional and negotiations with regard to disability, school integration and inclusion.